Design and implementation of inter-domain communication mechanism for high performance data processing - Мельник, Василь Михайлович; Пех, Петро Антонович; Мельник, Катерина Вікторівна; Багнюк, Наталія Володимирівна; Жигаревич, Оксана Костянтинівна (Eastern-European Journal of Enterprise Technologies, 2016)
The basic improvement in the computer operation is the involvement of multi-operating systems running on a physical computer. To make extensive use of virtualization technologies in cloud computing, the inter-domain communication effectiveness is a key factor for the functioning of distributed applications and some intensive network applications. The synchronous communication mechanism, used by the traditional virtual machine implementation mechanism based on the asynchronous signal fed by the virtual machine mechanism, often causes high latency and slow performance. The communication mechanism, called com-socket that uses interprocessor interrupts for synchronization and elimination of some unnecessary packet inspections is developed and implemented. The approach of using shared memory to reduce the data copying time is applied. The com-socket implementation is carried out on X86 in combination with the virtual machine mechanism. The study revealed that the com-socket has lower latency and higher performance compared to UNIX IPC.